Does external fixator pin site distance from definitive implant affect infection rate in pilon fractures?. Issue 2 (February 2019) - Hadeed, Michael M.; Evans, Cody L.; Werner, Brian C.; Novicoff, Wendy M.; Weiss, David B.
Highlights: Staged care has proven to be an effective treatment strategy for distal tibia pilon (AO/OTA Classification 43) fractures. Previous reports suggest an association between the overlap of ex-fix pin sites and definitive implants with deep infection. In this cohort, pin site distance from definitive implant location was not associated with an increase in deep infections. Abstract: Introduction: Tibial pilon fractures are often treated with initial external fixation followed by delayed definitive fixation. It has been postulated that the external fixator pin site may correlate with infection risk. The purpose of this study was to determine whether external fixator pin-site distance from definitive implants impacts the risk of deep infection in pilon fractures. Materials and methods: A retrospective cohort study was completed at a single level 1 trauma center. All patients ages 15–65 who underwent open reduction and internal fixation (ORIF) of a distal tibial fracture (AO/OTA Classification 43) from 2007 to 2013 were included. The final study population was 133 patients. The impact of external fixation pin location (relative to the definitive implant location) on postoperative infection was measured. Results: As a continuous variable, the distance between the closest pin site and plate was 62.1 ± 44.1 mm in the infected cohort and 62.2 ± 49.7 mm in the non-infected cohort (p = 0.991). Further analysis was performed by grouping the distances into less than 0 mm (i.e. overlapping), >0.0 – 25.0 mm, >25.0 – 50.0 mm, >50.0 – 75.0 mm, >75.0 – 100.0 mm, and >100.0 mm of separation. No significant differences were noted with regards to the risk for infection. Conclusions: Staged care has been shown to be an effective treatment strategy for AO/OTA type 43 fractures. There are many variables to consider when placing an external fixator construct. In this cohort, pin site distance from definitive implant location was not associated with an increase in deep infections. Level of evidence: Level III.